The Abundance of Nitrogen Fixing, Nitrifying, Denitrifying and Ammonifying Bacteria in the Soil of Tropical Rainforests and Oil Palm Plantations in Jambi - Zulfarina,; Rusmana, Iman; Mubarik, Nisa Rachmania; Santosa, Dwi Andreas (Makara Journal of Science, 2017)
Alterations in the use of land for oil palm plantations can change the domination and activity of soil bacteria. More specifically, alteration in soil microbial communities can directly affect soil ecosystem functioning, particularly with respect to carbon and nitrogen cycles. Nitrogen can be a limiting nutrient, and the availability of nitrogen in the soil environment becomes a major factor in controlling the production of biomass. This research project aimed at studying the abundance of nitrogen-fixing, nitrogen-oxidizing, nitrogen-reducing, and ammonifying bacteria based on their functional genes in the tropical rain forests of Taman Nasional Bukit Duabelas (TNBD) and the oil palm plantations in Sarolangun Jambi. Samples were collected in November 2015. Soil sampling was performed randomly at three points representing each area of ​​the tropical rainforests of TNBD and the seven- to eight-year-old oil palm plantations. Soil samples were collected using a soil sample core from 0–15 cm below the surface with depth strata of 0–5 cm, 5–10 cm, and 10–15 cm. Composite assessment was conducted on samples from each point corresponding to each respective depth strata. Soil samples were stored at -20ºC prior to testing. Microbial abundance was measured using the most probable number (MPN) method. The abundance of microbes that play a role in nitrogen metabolism between strata of 5–10 cm and 10–15 cm does not appear to be different. The highest abundance of microbes in oil palm plantation land in Jambi was found in samples with nitrifying bacteria, later followed by denitrifying, nitrogen-fixing, and ammonifying bacteria. Ultimately, it was found that microbial abundance in oil palm plantations was higher than the corresponding rates in samples from tropical rainforests.